Ammonium chloride catalyze sulfidation mechanism of smithsonite surface: Visual MINTEQ models, ToF-SIMS and DFT studies. (15th January 2020) - Bai, Shaojun; Yu, Pan; Ding, Zhan; Li, Chunlong; Xian, Yongjun; Wen, Shuming
Graphical abstract: Highlights: Deeper conversion from ZnS(aq), Zn2 S3 2− and Zn4 S6 4− ions to sphalerite occurs because of NH4 + ions catalysis action. The thickness of formed zinc sulfide species on samples is determined by ToF-SIMS analysis. NH3 acts a catalytic effect on the dehydroxylation of Zn(OH)2 through the formation of Zn(NH3 )4 2+ . NH3 promotes the sulphur migration from HS − to Zn with a lower energy barrier to form the ZnS spontaneously. Abstract: NH3 -based promoting sulfidation have attracted attention for smithsonite surface sulfidation, but the role of the NH3 /zinc/sulphur interface in promoting this chemistry remains under debate. Herein, we combined Visual MINTEQ models, ToF-SIMS and DFT to elucidate the impact of this interface on smithsonite surface sulfidation. The results demonstrated that the addition of ammonium chloride caused the CZnT in the pulp solution to increase. After the sulfidation reaction between zinc ammonium complex ions and HS − ions, accompanying the deeper conversion from ZnS(aq), Zn2 S3 2− and Zn4 S6 4− ions to sphalerite, more sphalerite was formed. ToF-SIMS analysis provided strong evidence for an increase in the zinc sulfide species on the smithsonite surface with the addition of NH4 Cl, and the thickness of formed zinc sulfide species was approximately 26.66 nm. DFT study confirmed that NH3 acted a catalytic role during the smithsonite surface sulfidation processing including ion-exchange reaction and sphalerite precipitation adsorption. The presence of NH3 changed the reaction pathway from Zn(OH)2  + HS −  → ZnS to Zn(OH)2  → Zn(NH3 )4 2+  + HS −  → ZnS and decreased the total energy barriers from 90.46 kcal/mol to 65.31 kcal/mol. Additionally, the NH3 promoted the sulphur migration from HS − to Zn with a lower energy barrier to form the ZnS spontaneously.